Psychometric Validation of the Multiple Sclerosis Environmental Supports Scale: A Brief Report. (April 2018) - Lee, Beatrice; Iwanaga, Kanako; Pfaller, Joseph; Chan, Fong; Chiu, Chungyi; Moser, Erin; Rumrill, Phillip
The main objective of this study was to evaluate the measurement structure of the Multiple Sclerosis Environmental Supports Scale (MSESS) with 248 individuals with multiple sclerosis (MS). Exploratory factor analysis yielded three reliable factors (health and mental health services; rehabilitation, social, and support services; and independent living supports). The MSESS appears to be a promising rehabilitation assessment tool for individuals with MS, one that can be used by rehabilitation counselors to evaluate environmental support factors in their interview, assessment, and rehabilitation planning protocols.